Methane Combustion over Lanthanum-based Perovskite Mixed Oxides - Arandiyan, Hamidreza. (Springer Theses, Recognizing Outstanding Ph.D. Research, 2015)
This book presents current research into the catalytic combustion of methane using perovskite-type oxides (ABO3). Catalytic combustion has been developed as a method of promoting efficient combustion with minimum pollutant formation as compared to conventional catalytic combustion. Recent theoretical and experimental studies have recommended that noble metals supported on (ABO3) with well-ordered porous networks show promising redox properties. Three-dimensionally ordered macroporous (3DOM) materials with interpenetrated and regular mesoporous systems have recently triggered enormous research activity due to their high surface areas, large pore volumes, uniform pore sizes, low cost, environmental benignity, and good chemical stability. These are all highly relevant in terms of the utilization of natural gas in light of recent catalytic innovations and technological advances. The book is of interest to all researchers active in utilization of natural gas with novel catalysts. The research covered comes from the most important industries and research centers in the field. The book serves not only as a text for researcher into catalytic combustion of methane, 3DOM perovskite mixed oxide, but also explores the field of green technologies by experts in academia and industry. This book will appeal to those interested in research on the environmental impact of combustion, materials and catalysis.